2010
DOI: 10.2174/187152710790966722
|View full text |Cite
|
Sign up to set email alerts
|

Editorial [Hot topic: Pharmacotherapies for Alcoholism: The Old and the New (Guest Editor: M. Foster Olive)]

Abstract: Alcoholism and other alcohol use disorders are major public health problems, and the success rates of non-pharmacological treatment of these disorders such as psychotherapy, cognitive-behavioral therapy, group therapy, or residential treatment programs,remain only modest at best. High rates of recidivism (relapse) in alcoholics attempting to remain abstinent are prevalent worldwide. In recent years abundant evidence has accumulated demonstrating that alcoholism is a complex and multifaceted disease of the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Approximately 90% of alcoholics experience at least one relapse over a 4-year period following treatment (Polich, 1981). Abstinence from alcohol drinking is an important goal for the treatment of alcoholism, but there is limited understanding of factors that influence risk of relapse and as a result few effective treatments (Olive, 2010, Zindel and Kranzler, 2014). Unfortunately, there are no controlled studies that have definitively shown either a single or combined intervention reliably prevents relapse to drinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 90% of alcoholics experience at least one relapse over a 4-year period following treatment (Polich, 1981). Abstinence from alcohol drinking is an important goal for the treatment of alcoholism, but there is limited understanding of factors that influence risk of relapse and as a result few effective treatments (Olive, 2010, Zindel and Kranzler, 2014). Unfortunately, there are no controlled studies that have definitively shown either a single or combined intervention reliably prevents relapse to drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments for alcohol dependence are at best only modestly effective (Olive, 2010, Zindel and Kranzler, 2014). Since individuals with alcohol dependence represent a clinically heterogeneous and genetically diverse population, it has been proposed that effective treatments should target specific phenotypes at distinct stages of addiction rather than employ a generic approach to all patients (Kuehn, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use disorder (AUD) is a chronic condition where sufferers may relapse even after periods of protracted abstinence (Olive, 2010). Gene expression and epigenetic changes following acute and chronic ethanol use and acute withdrawal have begun to be characterized (Gavin et al, 2016; Pandey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Naltrexone, a complete opioid antagonist, is a medication that blocks endogenous opioids released through the brain’s mesolimbic reward system (Pettinati & Rabinowitz, 2006), to reduce alcohol cravings in individuals with alcohol dependence (Olive, 2010; Richardson et al, 2008; Tambour & Quertemont, 2007). It is one of four evidence-based medication-assisted therapies (MAT) used to treat alcohol dependence (Garbutt, 2009; Williams, 2005).…”
Section: Introductionmentioning
confidence: 99%